2021
DOI: 10.3390/socsci10040138
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Urban Livability in Seoul, Korea: Urban Environmental Satisfaction and Neighborhood Relations

Abstract: This study examines the correlations between urban environmental satisfaction, neighborhood relations, and livability. Previous studies on livability have insufficiently dealt with urban environments and neighborhood relations and have failed to conduct an integrated analysis that considers the causal relationships between these factors. To fill these knowledge gaps, this study includes urban environmental satisfaction and neighborhood relations as factors affecting livability. Moreover, this study verified th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 41 publications
3
16
0
Order By: Relevance
“…Urban livability is reflected by (reflective indicators) from the most influential: social life, economy, and urban environment. This finding confirms similar research that neighbourhood relations influence urban livability (Lee, 2021). The finding also confirms that other factors may contribute to livability in the sub-districts, particularly factors that influence the urban environment variable.…”
Section: Structural Model Of Community Resilience and Livabilitysupporting
confidence: 89%
“…Urban livability is reflected by (reflective indicators) from the most influential: social life, economy, and urban environment. This finding confirms similar research that neighbourhood relations influence urban livability (Lee, 2021). The finding also confirms that other factors may contribute to livability in the sub-districts, particularly factors that influence the urban environment variable.…”
Section: Structural Model Of Community Resilience and Livabilitysupporting
confidence: 89%
“…Those authors also found that higher proportions of vegetation and the presence of trees mitigate the aforementioned negative effects. Trees were also seen by Basu et al (2022) to contribute to a more pleasant walking experience, while Lee (2021) argued, via a structural equation model, that large urban parks contribute to urban satisfaction. D’Acci (2014) approached pleasantness from a financial perspective, having found that more green areas and wider open spaces lead to higher real estate values.…”
Section: Discussionmentioning
confidence: 99%
“…Of the quantitative studies, only Calafiore (2020) and Li et al (2021) used field data to obtain a pleasantness indicator, respectively, a beauty index and a street quality index. Quantitative work exists on the impact of isolated geometric elements on pleasantness (Asgarzadeh et al, 2012; D’Acci, 2014; Lee, 2021; Wang et al, 2021), but none of these works have evaluated the combined landscape at the neighborhood scale. Thus, the literature on quantitative evaluation of layout pleasantness is very much in its infancy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it can precisely identify the cities and their corresponding urban boundaries by the iCN Model approach. The model applied the percolation theory (i.e., bond percolation) on the road intersection points to determine the urban agglomeration pattern of cities by utilizing the accessibility and locational proximity of the transportation network (Lee 2021). Then, it utilized Fractal Geometry to compute the maximum self-similarity distribution of percolation clusters, which calibrate the estimated urban agglomeration pattern with the current urban scale.…”
Section: Application Of the Icn Model To Identify Urban Boundariesmentioning
confidence: 99%
“…Cities are the outcome of the historical evolution of space, clustered and stacked according to the communities and resource agglomeration over many decades (Lee 2021). This integrated nature of city clusters form different city scales according to their degree of urban agglomeration, which have caused dramatic changes in the urban boundaries of cities.…”
Section: Introduction 1theoretical Background Of the Urban Boundary Demarcationmentioning
confidence: 99%